2022
DOI: 10.1021/acssuschemeng.1c07221
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Reconstruction of the Spinel Interface on a Li-Rich Layered Cathode Material with Enhanced Electrochemical Performances through HEPES and Heat Treatment Strategy

Abstract: The layered manganese-based lithium-rich oxide (LLO) cathode material is considered one of the most attractive cathode material candidates for next-generation lithium-ion batteries due to its high specific capacity. However, LLOs suffer from low coulombic efficiency as well as cycle capacity decay due to oxygen release and structural transformation during the first charge. Here, we report a simple method with 2-[4-(2-hydroxyethyl)-1-piperazinyl]­ethanesulfonic acid (HEPES) treatment combined with heat treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…30 The bending E g and stretching A 1g modes of the LiMO 2 phase can be validated in the peak positons at 485 and 591 cm −1 . 26,31 The Raman profiles of the LR-0 and LR-S samples showed the characteristic peaks of the Li 2 MnO 3 phase and the LiMO 2 component; however, the peaks at around 630−680 cm −1 are generated in the LR-S sample, indicating that the formation of the spinel structure can be confirmed by the Raman test. 26 At the same time, the refined Raman spectra of the LR-S sample showed that the content of the spinel structure in the LR-S sample is 4.67%, as shown in Figure S1 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 95%
“…30 The bending E g and stretching A 1g modes of the LiMO 2 phase can be validated in the peak positons at 485 and 591 cm −1 . 26,31 The Raman profiles of the LR-0 and LR-S samples showed the characteristic peaks of the Li 2 MnO 3 phase and the LiMO 2 component; however, the peaks at around 630−680 cm −1 are generated in the LR-S sample, indicating that the formation of the spinel structure can be confirmed by the Raman test. 26 At the same time, the refined Raman spectra of the LR-S sample showed that the content of the spinel structure in the LR-S sample is 4.67%, as shown in Figure S1 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 95%
“…), ion doping (Ce, 19 Nb, 20 S, 21 ) or thermal reduction (H 2 , 22 CO/CO 2 23 ), which can increase the initial Coulombic efficiency, improve the structural stability, and enhance the capacity retention ability. Sun et al 24 reduced part of Li 2 M-nO 3 (P-Li 2 MnO 3 ) to Li 2.1 Mn 0.9 O 2.79 by low-temperature reduction method with stearic acid, so as to introduce stacking faults, Vo and orthorhombic LiMnO 2 structures into the Li 2 MnO 3 phase (R-Li 2 MnO 3 ), and found that the introduction of Vo could not only increase the initial Coulombic efficiency (P-Li 2 MnO 3 : 33.6%; R-Li 2 MnO 3 : 77.1%), but also effectively accelerate the Li + diffusion in the material (P-Li 2 MnO 3 : 6.10 Â 10 À16 cm 2 s À1 ; R-Li 2 MnO 3 : 1.32 Â 10 À15 cm 2 s À1 ).…”
Section: Jiaoyang Chengmentioning
confidence: 99%
“…In addition, LiBOB 15 and FEC 16 were employed as electrolyte additives to form a stable conductive SEI film, which contributes to the improved interface stability and the alleviated voltage attenuation. Moreover, it has a remarkable significance in the introduction of Vo on the surface or in the bulk for LRMOs by gas–solid reaction (NH 4 HCO 3 , 17 NH 4 BF 4 18 ), ion doping (Ce, 19 Nb, 20 S, 21 ) or thermal reduction (H 2 , 22 CO/CO 2 23 ), which can increase the initial Coulombic efficiency, improve the structural stability, and enhance the capacity retention ability. Sun et al 24 reduced part of Li 2 MnO 3 (P-Li 2 MnO 3 ) to Li 2.1 Mn 0.9 O 2.79 by low-temperature reduction method with stearic acid, so as to introduce stacking faults, Vo and orthorhombic LiMnO 2 structures into the Li 2 MnO 3 phase (R-Li 2 MnO 3 ), and found that the introduction of Vo could not only increase the initial Coulombic efficiency (P-Li 2 MnO 3 : 33.6%; R-Li 2 MnO 3 : 77.1%), but also effectively accelerate the Li + diffusion in the material (P-Li 2 MnO 3 : 6.10 × 10 −16 cm 2 s −1 ; R-Li 2 MnO 3 : 1.32 × 10 −15 cm 2 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there is the degradation of the different components of the electrodes such as the binder, conductive additive, and the electrolyte. Several strategies have been adopted to stabilize the crystal structure and decrease the voltage and capacity drop of Li-rich NMC cathode material including surface coating, [31][32][33][34][35][36] doping, 29,[37][38][39][40][41][42][43][44][45] structural modication, [46][47][48][49][50][51][52][53] lithium extraction, [54][55][56][57] and electrolyte modication. [58][59][60][61][62][63][64] Controlling the cut-off voltage can be also an effective strategy for stabilizing the crystal structure and decreasing the capacity and voltage drop of Li-rich NMC cathode materials.…”
Section: Introductionmentioning
confidence: 99%